The dialectics of public security and the challenges to combat transnational crime in the framework of irregular wars (Research, Society and Development, 2020)
The following study aims to assess the perspective of transnational crime as a challenge to public security in the context of new combat tactics used by criminal organizations. The role of the Armed Forces and their use for such an undertaking is questioned for extrapolating the real attribute of the national Army as a guarantor of respect for the international system based on Westphalian sovereignty. The strategic plans adopted by the Brazilian State in particular have not been having an effect, mainly in the fight against drug trafficking, in which Brazil establishes itself as the second largest consumer of cocaine. The factor of territorial extension, wide borders and many points of departure for the Atlantic Ocean are factors that hinder the effectiveness in combating such activity. The adopted methodology is the empirical-analytical one, through qualitative methods, in order to demonstrate the new contemporary challenges due to the new paradigms of criminal action in Brazil and in the world. The conclusion is reached that the problem refers to a global socioeconomic issue, and that the treatment of this fight will be successful if it still insists on treating the effects instead of the causes.